ALOKASI PEMANFAATAN KREDIT USAHA RAKYAT (KUR) TERHADAP PERKEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) - Nur Bayti (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
This research is intended to analyse and evaluate the influences of the ulitization of people business credit program on the development of micro, small, medium enterprise at Bank Negara Indonesia Ltd, liability Company (Listed Company). Income is the dependent variable in tis research. The dependent variable consist of the costs of interest, the costs of employment, the costs raw materials, the costs of electricity and plumbing water, etc. The population of this research are the 818 debitors/receivers of the people Business Credit Program which are recomended in this distribution of the credit at Bank Negara Indonesia Ltd. Liability company (listed company) – branch office in Pontianak period of July 2017. The sample selection method is purposive sampling and the technique used in taking the samples is simple random sampling, there are 82 samples which have been collected. The research method used is multiple linear regression or Ordinary Linear Squares (OLS) the result of this show that (1) the interest costs have positive and significant effects on the income (2) the employment costs have positive and significant effects on the income (3) the costs of raw materials have positive and significant effects on the income (4) the costs of electricity and plumbing water have positive and significant effects on the income (5) the other costs  have no significant effects on the income.